Sex differences in the clinical features of 2,841 patients with migraine: a post-hoc, multicenter, cross-sectional study - Romozzi, Marina; Iannone, Luigi Francesco; Silvestro, Marcello; Paparella, Giulia; Scannicchio, Stefania; Battistini, Stefania; Ornello, Raffaele; Sacco, Simona; De Santis, Federico; Rainero, Innocenzo; Marcinnò, Andrea; Sebastianelli, Gabriele; et al. (Frontiers in Neurology, 2025)
BackgroundMigraine occurs two to three times more frequently in women than in men, exhibiting different clinical characteristics in both sexes. The present study aims to investigate further and extend the findings of sex-specific migraine phenotypes in a large cohort of subjects with migraine enrolled in the “Italian Headache Registry” (RICe).MethodsThis is a post-hoc analysis of prospectively collected data including subjects with episodic (EM) and chronic (CM) migraine, with or without medication-overuse headache (MOH), registered in the RICe database by 24 Italian headache centers. Migraine demographic and clinical characteristics were recorded, including quality and intensity of pain, pain localization at onset, concomitant symptoms, and monthly headache days (MHD).ResultsWe included 2,841 migraine subjects (80.0% women; mean age: 45.7 ± 14.3 years; mean MHDs 12.3 ± 9). Among them, 2,087 subjects had EM (73.5%), 754 (26.5%) had CM, and 273 (36.2%) had MOH. When considering individuals with EM and CM as a whole group, women reported higher pain intensity compared to men (NRS scale women [mean 7.6 ± 1.7] vs. men [7.0 ± 2.1], p = 0.006). This difference was also confirmed when comparing intensity categories (severe, moderate/severe, and moderate/mild) (p = 0.020). Moderate/mild attacks occurred more frequently in men than in women (14.9 vs. 7.7%, p = 0.0014). Furthermore, women reported more frequent migraine-associated symptoms such as photophobia/phonophobia (women: 72.7% vs. men: 62.3%, p = 0.006) and nausea/vomiting (women: 44.3% vs. men: 36.0%, p = 0.006). No sex differences were reported in terms of MHDs (p = 0.571) or baseline diagnoses (EM vs. CM, p = 0.269). Focusing on EM individuals, significant sex differences emerged in the summarized intensity categories (p = 0.012), as well as in the percentage of concomitant symptoms, which women more frequently reported.ConclusionWomen with EM or CM have higher pain intensity and more frequent concomitant migraine symptoms when compared to men. No sex-related differences were found in the frequency of MOH.